الدور الدع وي لأمهات المؤمنين في العهد النبوي "السيدة أمنا عائشة رضي الله عنها أنموذجا - حوامدي, حفيظة; السعدية قرفي, حليمة; حمتين, خولة; دليبة, كريمة (جامعة الوادي university of eloued, 2020)
يهدف هذا البحث إلى التعرف بالدور الدعوي للأمهات المؤمنين وبالأخص أمنا عائشة التي تعد من أمهات المؤمنين في رواية الحديث وفي الفقه والعلم، لذلك كانت دراستنا دقيقة بالنسبة في الدور الذي لعبته السيدة -رضي الله عنها- في عهد القدوة حيث تناولنا في البحث فصلين، كل فصل يحتوي على مبحثين وكل مبحث على ثلاث مطالب. فتناولنا في الفصل الأول بعض المفاهيم التي يقف عليها بحثنا حول الدعوة النسائية وأهميتها وتاريخها وأما في الفصل الثاني من البحث فاستعرضنا نموذج من داعيات العصر النبوي -رضي الله عنها- وهي أمنا عائشة التي قدمت دو راً فريدًا من نوعه في خدمت الدعوة في العصر النبوي وفي العصر الحديث. Abstract: This research aims to identify the role of advocacy for the mothers of believers .especially our mother Aisha ,which is one of the most important mothers of believers in the novel of hadith and in jurisprudence and science,so our study was accurate for what Mrs .aisha radhi played for god in the era of role models. Where we dealt in the research two chapters each chapter contains three demands,we addressd in the first chapter some of the concepts on which our research stands on women's advocacy and the second chapter of the research we presented a model of the call of the era the prophet is satisfied with god for them and she is our mother Aisha who presented a unique role in the service of advocacy in the old modern times.
دعوة